Logoterapi, Sebuah Upaya Pengembangan Spiritualitas Dan Makna Hidup Dalam Perspektif Psikologi Pendidikan Islam - Suyadi, Suyadi (Jurnal Pendidikan Islam, 2012)
Character education has become an important part of the national education system for character education has been positioned to be one step for curing social illness. However, it is still asked about what the content and process that will be done by the leaders of educational character of this nation. The moral values which are to be developed in the educational character of the nation of Indonesia consist of religious values, cultural values, and the values of Pancasila. Those are character educations which can be regarded as an authentic or specific character education in Indonesia.